Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/scs.0000000000007911
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Occipital Step-Off Deformities in Posterior Vault Distraction Osteogenesis

Abstract: Purpose: The goal of this study was to investigate patient specific factors and surgical techniques that affect occipital step-off deformity in children undergoing posterior vault distraction osteogenesis (PVDO). Methods: Patients who underwent PVDO were retrospectively reviewed and included if a high resolution three-dimensional computed tomography scan was available 1-year post-distractor removal. Two craniofacial surgeons were blinded to individual subjects and presented with 3 still images of three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…We did not account for the use of low occipital barrel staves in these cohorts because a previous study suggests outfractured segments do not contribute to additional volume. 12 Fifth, our results confirmed that posterior vault distraction osteogenesis and posterior vault reconstruction are deployed for different indications and goals, with posterior vault distraction osteogenesis most often for bicoronal craniosynostosis with emphasis on cranial volume expansion, and posterior vault reconstruction most often for sagittal craniosynostosis with emphasis on morphologic correction. Furthermore, we acknowledge the imprecision of estimated blood loss and transfusion thresholds and have used multiple measures to improve clinical accuracy.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We did not account for the use of low occipital barrel staves in these cohorts because a previous study suggests outfractured segments do not contribute to additional volume. 12 Fifth, our results confirmed that posterior vault distraction osteogenesis and posterior vault reconstruction are deployed for different indications and goals, with posterior vault distraction osteogenesis most often for bicoronal craniosynostosis with emphasis on cranial volume expansion, and posterior vault reconstruction most often for sagittal craniosynostosis with emphasis on morphologic correction. Furthermore, we acknowledge the imprecision of estimated blood loss and transfusion thresholds and have used multiple measures to improve clinical accuracy.…”
Section: Discussionsupporting
confidence: 74%
“…1–9 Although whole posterior vault reshaping is generally intended, multiple factors influence the position of the occipital osteotomy. A lower osteotomy has several potential advantages: it has been theorized to achieve more significant volumetric expansion and may more fully alleviate elevated intracranial pressure, 10–12 may better address a Chiari malformation if present, more holistically remodels the cranial vault, and may reduce step-off at the occiput. 13,14 However, a lower osteotomy at or below the torcula may increase the risk of transverse venous sinus injury or more extensive dural dissection with concomitant risks such as blood loss and instability.…”
mentioning
confidence: 99%
“…Zapatero et al found that patients with a supratorcular osteotomy had a higher risk of developing an occipital step-off deformity. 39 Several authors have attempted to minimize that deformity by performing a supratorcular osteotomy and adding barrel staves to the bone caudal to the osteotomy, 13,28,40 although evidence suggests that these barrel stave osteotomies do not help improve the step-off deformity. 17,34 In addition, infratorcular osteotomies may minimize the risk of injury to the torcula and bleeding, 3,9 although there is limited data to support that.…”
Section: Discussionmentioning
confidence: 99%